A Simple Manual Rosetting Method for Absolute CD4(+) Lymphocyte Counting in Resource-Limited Countries - Nouanthong, Phonethipsavanh (American Society for Microbiology, 2006)
A CD4 monoclonal antibody which reacts with CD4(+) lymphocytes but does not react significantly with monocytes was generated and used to develop a simple method for CD4 count. In a comparison with standard flow cytometry, high correlation was obtained. The developed method can be an alternative to flow cytometry for resource-limited countries.